Theoretical-methodological elements substantiating the role of investigation in the Professional Master’s Degree in Planning program of the Universidad Nacional - Láscarez Smith, Daniel (2021)
One of the main concerns expressed by students who are studying one of the two specializations of the Professional Master’s Degree in Planning (PMP)2 program is related, on the one hand, to the administrative and educational characteristics of the professional and academic master’s degrees, and on the other hand, to the scope and forms of the scientific research required in professional planning. As a result, in recent years, candidates for the master’s degree have experienced difficulties in clearly and successfully submitting their proposals for final graduation projects (FGP). This article presents the results of investigations on the relevance of scientific research in professional Planning contexts, carried out with students, curriculum experts and the faculty of the Professional Masters Degree in Planning (PMP). Using a qualitative methodology, important findings were obtained about the epistemological and technical difficulties encountered when proposing research in technical-professional environments. These findings can assist in improving the scientific-educational orientation of new students with regard to understanding the object of studying professional planning, and how applied research plays a fundamental role in the analysis of socio-political, economic and institutional contexts.